1999
DOI: 10.1046/j.1439-0523.1999.118001082.x
|View full text |Cite
|
Sign up to set email alerts
|

Male sterility in alloplasmic Brassica rapa L. carrying Eruca sativa cytoplasm

Abstract: For the development of a new cytoplasmic male sterility (CMS) system in Brassica rapa (2n= 20, AA), intergeneric hybridization was performed in Eruca sativa (2n= 22, EE)×B. rapa. The original amphihaploid F1 plant (2n= 21, EA) generated via embryo rescue produced a sesquidiploid F1 plant (2n= 31, EAA), from which the alloplasmic F3 plants were generated. In F3, some progenies with malformed anthers were maintained as male‐sterile lines up to the F5 generation. In the F6 and F7 generations, the alloplasmic male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…The second part was done to verify the result of the first part, resulting in similar observations. Many alloplasmic lines with cytoplasmic male sterility have been developed by substitution backcrosses in interspecific or intergeneric hybrids (Pearson 1972;Bannerot et al 1977;Hinata and Konno 1979;Prakash and Chopra 1990;Sigareva and Earle 1997;Matsuzawa et al 1999). In this experiment, male sterility was observed only in the interspecific F 1 , BC 1 and BC 2 generations of plants with the N-cytoplasm (Fig.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…The second part was done to verify the result of the first part, resulting in similar observations. Many alloplasmic lines with cytoplasmic male sterility have been developed by substitution backcrosses in interspecific or intergeneric hybrids (Pearson 1972;Bannerot et al 1977;Hinata and Konno 1979;Prakash and Chopra 1990;Sigareva and Earle 1997;Matsuzawa et al 1999). In this experiment, male sterility was observed only in the interspecific F 1 , BC 1 and BC 2 generations of plants with the N-cytoplasm (Fig.…”
Section: Discussionmentioning
confidence: 81%
“…The effect of cytoplasm-nucleus substitution in different species of Brassica was first reported by Mizushima and Katsuo (1958), while the use of alloplasmic individuals in plant breeding was proposed by Mizushima (1961). The alloplasmic effects may have practical advantages, such as the cytoplasmic male sterility (Pearson 1972;Hinata and Konno 1979;Matsuzawa et al 1999;Prakash et al 2001), elimination of self-incompatibility (Mizushima and Katsuo 1958), enhancement of herbicide resistance (Beversdorf et al 1980), improved disease resistance (Banga et al 1984) and the introgression of fertility restorer gene(s) ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6C). These structures resemble the thirdwhorl filamentous organs observed in several Arabidopsis mutants including ufo (Wilkinson and Haughn, 1995), afo (Kumaran et al, 1999), and fil (Sawa et al, 1999), and have also been observed in species hybrids (Michaelis, 1954;Malik et al, 1999;Matsuzuwa et al, 1999).…”
Section: Variation For Developmental Traits and Chromosome Assortmentmentioning
confidence: 69%
“…For example, the whole range of nine turnips marketed by the Musashino Seed Co. Ltd. are F 1 hybrids. Cytoplasmic male sterility is also available in B. rapa, either derived from cytoplasms used in oil seed rape (Hu et al, 1997;Sovero, 1988;Verma et al, 2000) or from new cytoplasms (Okawa, 1985;Matsuzawa et al, 1999;Deol et al, 2003).…”
Section: F 1 Hybrid Breedingmentioning
confidence: 99%